PARTICIPATORY EMPOWERMENT OF SELF-CARE GROUPS FOR PERSONS AFFECTED BY LEPROSY WITH DISABILITIES - Bakhtiar, Rahmat; Duma, Krispinus; Sukmana, Mayusef; Tarihoran, Nurhasan; Kabir, Fahmi (Universitas Padjadjaran, 2026)
Disability and stigma among persons affected by leprosy remain important public health challenges, particularly for those living with permanent impairments. These conditions can limit physical functioning, social participation, economic independence, and overall quality of life. This community engagement program aimed to improve knowledge of self-care and disability prevention, as well as enhance the quality of life of persons affected by leprosy through a community-based empowerment approach. The program was conducted in Harapan Baru Sub-village, Sebulu Village, Kutai Kartanegara Regency, East Kalimantan, Indonesia, from May to August 2025. A total of 25 persons affected by leprosy participated, including 76% with grade 2 disability and 24% with grade 1 disability. The intervention consisted of health education, self-care training, and empowerment activities designed to promote independence and improve quality of life. Knowledge and quality of life were assessed before and after the intervention using a structured questionnaire and the Assessment of Quality of Life–4 Dimensions (AQoL-4D) instrument. The results showed improvements in both knowledge and quality of life following the intervention. The proportion of participants with high self-care knowledge increased from 4% to 36%, while the proportion with low knowledge of disability prevention decreased from 48% to 32%. Quality of life also improved, as indicated by a reduction in the proportion of participants with a high level of quality-of-life impairment from 40% to 12%. In contrast, the proportions of participants with moderate and low levels of impairment increased from 40% to 56% and from 20% to 32%, respectively. Community-based empowerment interventions that integrate health education, self-care training, and community participation can improve knowledge and quality of life among persons affected by leprosy. Sustained support from relevant stakeholders is needed to maintain independence, reduce stigma, and enhance the well-being of persons affected by leprosy.Kecacatan dan stigma pada penyintas kusta masih menjadi tantangan kesehatan masyarakat karena dapat membatasi fungsi fisik, partisipasi sosial, kemandirian ekonomi, dan kualitas hidup. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pengetahuan tentang perawatan diri dan pencegahan kecacatan serta meningkatkan kualitas hidup penyintas kusta melalui pendekatan pemberdayaan berbasis masyarakat. Kegiatan dilaksanakan di Dusun Harapan Baru, Desa Sebulu, Kabupaten Kutai Kartanegara, Kalimantan Timur, pada Mei–Agustus 2025. Sebanyak 25 penyintas kusta berpartisipasi, terdiri atas 76% dengan cacat tingkat 2 dan 24% dengan cacat tingkat 1. Intervensi meliputi pendidikan kesehatan, pelatihan perawatan diri, dan kegiatan pemberdayaan untuk meningkatkan kemandirian serta kualitas hidup. Pengetahuan dan kualitas hidup diukur sebelum dan sesudah intervensi menggunakan kuesioner terstruktur dan instrumen Assessment of Quality of Life-4 Dimensions (AQoL-4D). Hasil menunjukkan adanya peningkatan pengetahuan dan kualitas hidup setelah intervensi. Proporsi peserta dengan tingkat pengetahuan tinggi mengenai perawatan diri meningkat dari 4% menjadi 36%, sedangkan peserta dengan pengetahuan rendah mengenai pencegahan kecacatan menurun dari 48% menjadi 32%. Pada aspek kualitas hidup, proporsi peserta dengan gangguan kualitas hidup tinggi menurun dari 40% menjadi 12%, sementara kategori gangguan sedang meningkat dari 40% menjadi 56% dan kategori gangguan rendah meningkat dari 20% menjadi 32%. Intervensi pemberdayaan berbasis masyarakat yang mengintegrasikan pendidikan kesehatan, pelatihan perawatan diri, dan keterlibatan masyarakat efektif meningkatkan pengetahuan dan kualitas hidup penyintas kusta. Dukungan berkelanjutan dari berbagai pemangku kepentingan diperlukan untuk mempertahankan kemandirian, mengurangi stigma, dan meningkatkan kesejahteraan penyintas kusta.